1998
DOI: 10.1111/j.1151-2916.1998.tb02780.x
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Silicoboron Carbonitride Ceramic with Very High Viscosity at Temperatures above 1500°C

Abstract: Recently, the viscosity of a predominantly amorphous silicon carbonitride (Si 1.7 C 1.0±0.1 N 1.5 ) alloy with an apparent glass-transition temperature (T g ) of 1400°-1500°C was studied. In this study, the creep behavior of silicoboron carbonitride (Si 2 B 1.0 C 3.4 N 2.3 ), which seems to have a T g value of >1700°C, was examined. Both materials exhibited a threestage creep behavior. In stage I, the creep rate declined, because of densification. In stage II, the strain rate approaches a steady state. In stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
113
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(116 citation statements)
references
References 17 publications
2
113
0
1
Order By: Relevance
“…The result of X-ray diffraction of the Si-B-C-N specimens after the creep tests by Riedel et al was not significantly altered as compared with the starting material. 14) Such increasing of viscosity without crystallization has been observed in other amorphous materials and usually explained by using free volume models. 25) Baufeld et al discussed that the increase of the flow stress was related to the decrease of free volume in the amorphous phase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The result of X-ray diffraction of the Si-B-C-N specimens after the creep tests by Riedel et al was not significantly altered as compared with the starting material. 14) Such increasing of viscosity without crystallization has been observed in other amorphous materials and usually explained by using free volume models. 25) Baufeld et al discussed that the increase of the flow stress was related to the decrease of free volume in the amorphous phase.…”
Section: Discussionmentioning
confidence: 99%
“…12,[14][15][16][17] This volume change of the specimen makes it difficult to separate the intrinsic plastic deformation of the amorphous materials from the total deformation. The strain rate of those Si-B-C-N materials decreased with time in the creep tests, while the flow stress increased with strain in the compression tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12] The high temperature stability of amorphous Si 3 N 4 -based materials strongly depends on additional elements such as boron and carbon. Baldus et al reported that amorphous Si-B-N and Si-B-C-N materials retain amorphous up to 1700…”
Section: Introductionmentioning
confidence: 99%